Diseases caused by poxvirus - orf and milker's nodules: a review - Barraviera, S.r.c.s. [UNESP] (2005)
Sheep and cattle parapoxviruses cause in human beings diseases of very similar aspect, named orf and milker's nodules, respectively. These infections are generically called farmyard pox. In the present article, we show the epidemiological, clinical, and histopathological aspects, as well as the treatment of these two viral diseases that are very similar, being differentiated only by their epidemiological aspects.